30.2k views
0 votes
Indicate a general rule for the nth term of the sequence a1 = 2 and r = √3.

an = (√3)(2)^n+1
an = (√3)(2)^n-1
an = (2)(√3)^n-1
an = (2)(√3)^n+1

User Charlie
by
5.4k points

2 Answers

1 vote

Answer:

the correct answer is an = (2)(√3)^n-1

User Roy Goode
by
6.7k points
2 votes

It is given in the question that,


a_(1) = 2, r = \sqrt 3

Since we have the value of r given, so we have to use the formula to find the nth term of the geometric progression, which is


a_(n) = a(r)^(n-1)

Substituting the values of a and r, we will get


a_(n) = 2( \sqrt 3)^(n-1)

So the correct option is the third option .

User FlyingAssistant
by
5.7k points